2007
DOI: 10.1007/s00299-007-0395-7
|View full text |Cite
|
Sign up to set email alerts
|

Two rice cytosolic ascorbate peroxidases differentially improve salt tolerance in transgenic Arabidopsis

Abstract: In order to determine the different roles of rice (Oryza sativa L.) cytosolic ascorbate peroxidases (OsAPXa and OsAPXb, GenBank accession nos. D45423 and AB053297, respectively) under salt stress, transgenic Arabidopsis plants over-expressing OsAPXa or OsAPXb were generated, and they all exhibited increased tolerance to salt stress compared to wild-type plants. Moreover, transgenic lines over-expressing OsAPXb showed higher salt tolerance than OsAPXa transgenic lines as indicated by root length and total chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(84 citation statements)
references
References 31 publications
4
78
0
1
Order By: Relevance
“…systems, which modulates protection from high light and a combination of drought and heat (Davletova et al, 2005a;Koussevitzky et al, 2008). Overexpression of rice APX1 and APX2 in Arabidopsis reduces the accumulation of hydrogen peroxide, restricts chlorophyll degradation, and enhances survival under salinity stress (Lu et al, 2007). We determined that the accumulation of both APX1 and APX2 mRNAs was upregulated by methyl viologen treatment in M202 and M202(Sub1), but the induction was more pronounced in the SUB1 genotype ( Figure 8).…”
Section: Sub1a Enhances Oxidative Stress Tolerancementioning
confidence: 99%
“…systems, which modulates protection from high light and a combination of drought and heat (Davletova et al, 2005a;Koussevitzky et al, 2008). Overexpression of rice APX1 and APX2 in Arabidopsis reduces the accumulation of hydrogen peroxide, restricts chlorophyll degradation, and enhances survival under salinity stress (Lu et al, 2007). We determined that the accumulation of both APX1 and APX2 mRNAs was upregulated by methyl viologen treatment in M202 and M202(Sub1), but the induction was more pronounced in the SUB1 genotype ( Figure 8).…”
Section: Sub1a Enhances Oxidative Stress Tolerancementioning
confidence: 99%
“…The previous study found the Apx genes in rice leaves showed a difference of their transcription in response to the abiotic stress [14,29]. Increase in tolerance against salinity stress was observed in Arabidopsis plant overexpressed with cApx gene [30]. The different transcription level of Apc gene(s) indicated that a variation of oxidative defence mechanism was developed depending on the type and level of the abiotic stress.…”
Section: The Apx Gene Expressionmentioning
confidence: 99%
“…Expression analysis reveals that OsAPX2 is upregulated by salt [168]. Arabidopsis plants expressing OsAPX2 exhibit higher ROS-scavenging activity and salt tolerance than those expressing OsAPX1 [104].…”
Section: Functional Proteinsmentioning
confidence: 99%